Pengorganisasian Pesan Dakwah Da’i Selebriti Ustad Al Habsy - Budi Ariyanto (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2019)
Indonesian society is currently experiencing changes in the context of the missionary movement. A da’i celebrity in her missionary activities has not been oriented towards the resulting impact. Research on organizing da’i's da'wah message has the purpose of knowing the organization of messages in preaching. Based on the theme raised in this study formulate a problem about how to construct da'wah messages, how to form Al Habsyi's da'wah messages. Relevant to the objectives, this study uses qualitative methods with a case study approach. Da'wah messages conveyed by cleric Al Habsyi namely mubasyaroh. Organizing messages by increasing the attention of mad’u, through nasyid, the needs of mad’u, fulfillment of the material of mad’u preaching on religious messages, describes the contents of the message of da'wah, through stories. Utilizing stories and taking actions with persuasive communication, namely by carrying out the Sunnah.AbstrakMasyarakat Indonesia saat ini mengalami perubahan dalam konteks gerakan dakwah. Seorang da’i selebriti dalam kegiatan dakwahnya belum berorientasi pada dampak yang dihasilkan. Penelitian tentang pengorganisasian pesan dakwah da’i selebriti ini memiliki tujuan untuk mengetahui pengorganisasian pesan dalam berdakwah. Berdasarkan tema yang diangkat dalam penelitian ini merumuskan masalah tentang bagaimana konstruk pesan dakwah, bagaimana merumuskan pesan dakwah Al Habsyi. Relevan dengan tujuan, penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Pesan dakwah yang disampaikan ustad Al Habsyi yaitu secara mubasyaroh. Pengorganisasian pesan dengan meningkatkan perhatian mad’u, melalui nasyid, kebutuhan mad’u, pemenuhan materi dakwah mad’u atas pesan agama, menggambarkan isi pesan dakwah, melalui kisah. Pemanfaatan kisah dan melakukan tindakan dengan komunikasi yang bersifat persuasif, yaitu dengan menjalankan sunnahnya..